The Reduction of Anxiety and Improved Maternal Attachment to Fetuses and Neonates by Relaxation Training in Primigravida Women - Monire Toosi; Marzieh Akbarzadeh; Farkhondeh Sharif; Najaf Zare (Women’s Health Bulletin, 2014)
Background: Anxiety is among the pregnancy complications affecting maternal mental and physical health and attachment to the fetus and newborn. Relaxation training is an effective, simple and available method to address this dismal condition. Objectives: The aim of this study was to evaluate the effect of relaxation training on anxiety and maternal attachment to fetus and neonate in primigravida women. Materials and Methods: This clinical trial comprised 84 primigravida pregnant woman including 42 experimental and 42 controls from a population of pregnant women referred to Shushtari and Hafez hospitals in the summer of 2010. Before the beginning of the study, anxiety and attachment levels of mothers to the fetus were assessed in both groups. In addition to the routine prenatal cares, the experimental group underwent four weekly 90-minutes of relaxation training for one month. The control group received only standard care during pregnancy. At the end of one month intervention, the anxiety and attachment levels of mothers to the fetus were assessed in both groups. The researcher visited mothers, while breastfeeding, on the first day after delivery, and recorded the mothers-neonates attachment behaviors. Results: The two groups were homogeneous in terms of age, sex and attachment and anxiety levels before the intervention. There were no significant differences in mean score of anxiety (P = 0.618) and attachment (P = 0.897) levels before the intervention in both groups. However, significant differences were observed in the anxiety (P = 0.017) and attachment (P = 0.005) mean scores after the intervention between both groups. Also, the mean score of maternal attachment after the first breastfeeding in the two groups showed a statistically significant difference (P < 0.0001). Conclusions: The results of this study showed that relaxation training reduces anxiety in pregnant women and improves maternal attachment to the newborn.